Analisis Kaidah Al-‘Ādah Muḥakkamah Terhadap Praktik Kesepakatan Lisan (Tukar dan Jual) dalam Transaksi Sehari-Hari Masyarakat Hulu Sungai Kalimantan Selatan - Muliana Muliana; Siti Anida; Lahmudinur Lahmudinur (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
‘Urf Sahih This study discusses the application of the principle of al-‘ādah muḥakkamah to the practice of verbal agreements using the expressions “exchange” and “sell” in everyday transactions among the Hulu Sungai community in South Kalimantan. The study aims to analyze the validity of this practice from an Islamic legal perspective. The method used is qualitative research with a descriptive-analytical approach through a normative approach and case studies. The results show that the practice of verbal transactions carried out based on community customs can be categorized as ‘urf sahih because they contain elements of willingness, clarity, and social recognition. Islamic law also allows for local traditions in the practice of muamalah as long as they do not conflict with sharia and do not contain elements of usury, gharar, fraud, and coercion. Thus, the principle of al-‘ādah muḥakkamah becomes an important foundation in understanding the relationship between Islamic law and community customs.